2013
DOI: 10.1063/1.4820770
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial integration of dilute magnetic semiconductor Sr3SnO with Si (001)

Abstract: Epitaxial thin films heterostructures of topological insulator candidate Sr3SnO (SSO) are grown on a cubic yttria-stabilized zirconia (c-YSZ)/Si (001) platform by pulsed laser deposition. X-ray and electron diffraction patterns confirm the epitaxial nature of the layers with cube-on-cube orientation relationship: (001)[100]SSO∥(001)[100]c-YSZ∥(001)[100]Si. The temperature dependent electrical resistivity shows semiconductor behavior with a transport mechanism following the variable-range-hopping model. The SSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 18 publications
3
41
2
Order By: Relevance
“…It is also worth noting that experiments on this series of materials are now developing. We have highly refined crystal characterization [28], thin film fabrication [29,30], a thermal measurement [31], and even a report of superconductivity [32].In this paper, we show that the competition between SOC and the band overlap leads to an interesting evolution of the band structure, taking Ba 3 SnO as a prototypical example. In the previous work on the analysis of the antiperovskite family [24], we regarded that the SOC arXiv:1705.08934v1 [cond-mat.mes-hall]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that experiments on this series of materials are now developing. We have highly refined crystal characterization [28], thin film fabrication [29,30], a thermal measurement [31], and even a report of superconductivity [32].In this paper, we show that the competition between SOC and the band overlap leads to an interesting evolution of the band structure, taking Ba 3 SnO as a prototypical example. In the previous work on the analysis of the antiperovskite family [24], we regarded that the SOC arXiv:1705.08934v1 [cond-mat.mes-hall]…”
mentioning
confidence: 99%
“…It is also worth noting that experiments on this series of materials are now developing. We have highly refined crystal characterization [28], thin film fabrication [29,30], a thermal measurement [31], and even a report of superconductivity [32].…”
mentioning
confidence: 99%
“…Researchers at North Carolina State University have created a new compound that can be integrated into silicon chips and is a dilute magnetic semiconductor [1,2], meaning that it could be used to make "spintronic" devices, which rely on magnetic force to operate, rather than electrical currents. The researchers synthesized the new compound, strontium tin oxide (Sr 3 SnO), as an epitaxial thin film on a silicon chip.…”
Section: Introductionmentioning
confidence: 99%
“…F. Lee et al [9][10][11] successfully managed to grow epitaxial Sr3SnO (SSO) one of the predicted TI film on Si based substrate by means of pulsed leaser deposition (PLD). The new inverse-perovskites (SSO) turned to exhibit a ferromagnetic state at room temperature, which will pave the way toward integrating the spin degree of freedom in silicon based electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study on Sr 3 SnO thin film grown by pulsed-laser deposition showed a semiconducting behavior with a magnetic ground state. 24 However, the growth of Sr 3 SnO anti-perovskite films may need further investigation because x-ray diffraction (XRD) did not show Bragg reflections from (00l) plane with odd l expected for anti-perovskite, and XRD peaks assigned to Sr 3 SnO were not distinguishable from those of yttria-doped zirconia (YSZ) used as a buffer layer.…”
mentioning
confidence: 99%